ANALISIS FAKTOR YANG MEMPENGARUHI IMPLEMENTASI KEBIJAKAN PENERTIBAN DAN PEMBINAAN GELANDANGAN DAN PENGEMIS DI KOTA PEKANBARU - Dia Meirina Suri (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
The policy of ordering and fostering homeless and beggars in Pekanbaru City was made to overcome the problem of homeless and beggars who have become phenomena and has become a very complex issue. This condition makes people become disturbed, homeless and beggars use various ways to make people feel sorry for them. They begged by reaching out even they dare to pretend defect in order to get the mercy of the community, other than that which is very disturbing community is the act of coercion that they do on the highway, especially red lights. The policies that have been made have not had an impact on their existence, the number of homeless and beggars is increasing every year. The purpose of this study is to see what factors affect the implementation of policy of curbing homelessness and beggars in Pekanbaru City. This research uses qualitative approach and analyzed descriptively. The results of the study found that the factors that influence it are the policy itself, the institution factor and or the implementing agency and environmental factors.